Analysis of Students Problem Solving Abilities Using Contextual Learning on Colloid Material at SMAS Pertiwi - Annisa Rahayu; Iis Siti Jahro (Universitas Negeri Medan, 2024)
Many students do not have good problem solving skills in solving problems in everyday life, especially in chemistry learning. Therefore, analysis of students' problem solving abilities is needed to determine the level of problem solving abilities in chemistry learning, especially in colloidal systems material in everyday life. The purpose of this study is to describe how students use cooperative learning, specifically contextual learning, to solve problems. The goals of this study will be accomplished since the data collected will take the shape of words or utterances derived from the outcomes of interviews and Polya's problem-solving abilities. The use of this innovative learning media is supported by a contextual learning model. The type of research used in this study is qualitative research with a descriptive approach. This research procedure includes: (1) preparation stage; (2) implementation stage and (3) Final Stage. The problem solving ability of class XI students of SMAS Pertiwi Medan is at the